Garra dohjei, a new species of labeonine fish (Teleostei: Cyprinidae) from Meghalaya, India - Marngar, Ibansiewdor; Mawlong, Batngenlang; Lokeshwor, Yumnam (Zootaxa, 2024)
Garra dohjei, a new labeonine fish with transverse lobe and incipient proboscis is described from the Ñiangdai, a tributary of the Brahmaputra River, Meghalaya, India. The new species is distinguished from its congeners with transverse lobe and incipient proboscis, in having a well-developed transverse lobe with around 9–12 minute tubercles, deep transverse groove between transverse lobe and incipient proboscis, black spot immediately anterior to upper angle of gill opening, 5–6 dark black stripes on caudal peduncle, 33–35 lateral line scales, 9–10 predorsal scales, 16–circumpeduncular scales, 15 branched pectoral-fin rays, and total vertebrae 33.